1987
DOI: 10.1104/pp.84.3.872
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Freezing Tolerance in Spinach Is Associated with the Synthesis of Cold Acclimation Induced Proteins

Abstract: Spinach (Spinacia okracca L. cv Bloomsdale) seedlings cultured in vitro were used to study changes in protein synthesis during cold accfimation. Seedlings grown for 3 weeks postsowing on an inorganic-nutrientagar medium were able to increase their freezing tolerance when grown at 5°C. During cold acclimation at 5°C and deaccfimation at 25°C, the kinetics of freezing tolerance induction and loss were similar to that of soil-grown plants. Freezing tolerance increased after 1 day of cold acclimation and reached a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 24 publications
1
65
1
2
Order By: Relevance
“…After focusing, the fractions were collected and pH values determined. SDS-PAGE analyses revealed that free-solution-isoelectric focused fractions closely approximated analytical two-dimensional separations (12) for spinach cold acclimation proteins, which facilitated identification of fractions containing CAP79. 2 Fractions most enriched for CAP79 were selected for further purification.…”
Section: Protein Purificationmentioning
confidence: 85%
See 3 more Smart Citations
“…After focusing, the fractions were collected and pH values determined. SDS-PAGE analyses revealed that free-solution-isoelectric focused fractions closely approximated analytical two-dimensional separations (12) for spinach cold acclimation proteins, which facilitated identification of fractions containing CAP79. 2 Fractions most enriched for CAP79 were selected for further purification.…”
Section: Protein Purificationmentioning
confidence: 85%
“…Spinach seedlings (Spinacia oleracea L. cv Bloomsdale) were grown from seed in a controlled environment as previously described (12). Cold acclimation and deacclimation treatments were conducted with a 12-h photoperiod as previously described (12).…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, however, it is interesting to note the work of Guy et al (7,9). These investigators have shown that gene expression is altered during cold hardening of spinach and that one of the 'cold acclimation proteins' was a large acidic polypeptide with a mol wt of about 160 kD and pI about 4.5.…”
Section: Discussionmentioning
confidence: 99%